Comparative ex vivo activity of novel endoperoxides in multidrug-resistant plasmodium falciparum and P. vivax. - Marfurt, J; Chalfein, F; Prayoga, P; Wabiser, F; Wirjanata, G; Sebayang, B; Piera, K; Wittlin, S; Haynes, R; Möhrle, J; Anstey, N; Kenangalem, E; et al. (2012)
The declining efficacy of artemisinin derivatives against Plasmodium falciparum highlights the urgent need to identify alternative highly potent compounds for the treatment of malaria. In Papua Indonesia, where multidrug resistance has been documented against both P. falciparum and P. vivax malaria, comparative ex vivo antimalarial activity against Plasmodium isolates was assessed for the artemisinin derivatives artesunate (AS) and dihydroartemisinin (DHA), the synthetic peroxides OZ277 and OZ439, the semisynthetic 10-alkylaminoartemisinin derivatives artemisone and artemiside, and the conventional antimalarial drugs chloroquine (CQ), amodiaquine (AQ), and piperaquine (PIP). Ex vivo drug susceptibility was assessed in 46 field isolates (25 P. falciparum and 21 P. vivax). The novel endoperoxide compounds exhibited potent ex vivo activity against both species, but significant differences in intrinsic activity were observed. Compared to AS and its active metabolite DHA, all the novel compounds showed lower or equal 50% inhibitory concentrations (IC(50)s) in both species (median IC(50)s between 1.9 and 3.6 nM in P. falciparum and 0.7 and 4.6 nM in P. vivax). The antiplasmodial activity of novel endoperoxides showed different cross-susceptibility patterns in the two Plasmodium species: whereas their ex vivo activity correlated positively with CQ, PIP, AS, and DHA in P. falciparum, the same was not apparent in P. vivax. The current study demonstrates for the first time potent activity of novel endoperoxides against drug-resistant P. vivax. The high activity against drug-resistant strains of both Plasmodium species confirms these compounds to be promising candidates for future artemisinin-based combination therapy (ACT) regimens in regions of coendemicity.